МƏНАЎИЯТ – ИНСАН ТƏРБИЯСЫНЫҢ ӨЗЕГИ - Абаев, С.; Якубов, М.А.; Алламбергенов, Е. (FAN va JAMIYAT, 2021)
Based on the works of President Shavkat Mirziyoyev, the article analyzes the essence and content of the concept "spirituality", its meaning for every person and society. It also shows the ongoing activities in the country to build a New Uzbekistan and the foundations of the Third Renaissance.